Faktor-Faktor yang Mempengaruhi Return Saham: Studi Industri Barang Konsumsi yang Listing di BEI - umi solechah; Ayu Noviani Hanum; Alwiyah Alwiyah; Hardiwinoto Hardiwinoto; Raden Ery Wibowo (Universitas Muhammadiyah Semarang, 2020)
This research to analyze the influence of Current Ratio, Debt to Equity Ratio and Return On Asset simultaneously and partially to stock return of manufacturing company sectors of Consumer Goods Industry listed on Indonesia Stock Exchange (IDX) period 2015-2019. Sampling in this research uses the purposive sampling method. The population in this research is a manufacturing company sectors of Consumer Goods Industry listed on the Indonesia Stock Exchange (IDX) period 2015-2019. Total population of 53 companies and companies that meet the criteria as a sample as many as 23 companies. The period of observation in this research for 5. years from 2015-2019. The analytical techniques used are multiple regression analyses. The results showed that Return On Assets (ROA) have a partially effect that is positive and significant to stock return. The Current Ratio (CR) and Debt to Equity Ratio (DER) have a partially effect that is negative and significant to stock return. While simultaneously the Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Assets (ROA) influence the stock return. The result of determination coefficient (R2) showed that Current Ratio (CR), Debt To Equity Ratio (DER), and Return On Assets (ROA) in explaining the stock return was 33,6 % and the rest was explained by other unexamined variable in this research.